Chemmotology problems on the threshold of third millennium - Карабиов, Г. П.; Хлистун, Л. П.; Бейко, Ю. О.; Вовк, В. І.; Жуков, В. М.; Алатірьова, Т. В. (Proceedings of National Aviation University (archive), 2000)
It is underlined that the main chemmotology problem in the nearest future will be a complex solution of fundamental and applied problems directed on economical and rational use of fuels, oils, lubricants, technical liquids and related products of petroleum origin